Host-probiotic interaction: new insight into the role of the endocannabinoid system by in vivo and ex vivo approaches - Giorgia Gioacchini (Nature Portfolio, 2017)
Abstract The endocannabinoid system plays an important role in regulating inflammation in several chronic or anomalous gut inflammatory diseases. In vivo and ex vivo studies showed that 30 days treatment with a probiotic mix activated the endocannabinoid system in zebrafish. These results highlight the potential of this probiotic mixture to regulate immune cell function, by inducing gene expression of toll-like receptors and other immune related molecules. Furthermore, TUNEL assay showed a decrease in the number of apoptotic cells, and this finding was supported by a reduction in pro-apoptotic factors and an increase in anti-apoptotic molecules. The results presented here strengthen the molecular mechanisms activated by probiotic mix controlling immune response and inflammation.